The Role of WhatsApp for Madrasah Ibtidaiyah Teachers in Online Learning during the Covid-19 Pandemic - Ianatut Thoifah (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2021)
This research aims to determine the role of the WhatsApp application in online learning during COVID-19 pandemic. This research uses a descriptive qualitative approach. The analysis uses the Miles Huberman and Saldana model, researchers explore data using google form to 27 respondents consisting of MI teachers in Soko-Tuban. The results of this research indicate that the use of the WhatsApp application can act as an alternative solution to online learning problems, although not all problems can be solved by using WhatsApp application, however, WhatsApp application plays a role in 6 of the 16 online learning problems in MI teachers in Soko Tuban. The problems that can be solved by using WhatsApp application are 1) the implementation of the distance learning process is not yet ready; 2) lack of mastery of technology for parents, educators, and students; 3) lack of student interest in online learning; 4) Less than optimal delivery of material using online media; 5) limited time for teaching and learning process; and 6) lack of communication between students, educators and parents. These results are expected to be an evaluation of the extent to which the use of WhatsApp application plays a role in problems online learning, besides that teachers and all related components can maximize the use of the WhatsApp application as an alternative solution to some of the existing problems.